South of the Sahara : development in African economies - Schatz, Sayre P. (London : Macmillan [for] Temple University, 1972)
The book includes papers presented at a conference on African economic development at Temple University. The papers are grouped under four heads: indigenous entrepreneurship and trade; agriculture and industry; economic policy and finance; and international economic relations. No contributor attempts a general appraisal of the African situation; no real assessment is made of the experience of the individual countries on which the studies concentrate.
"... papers at a conference on African economic development at Temple University toward the end of the decade [1960s]."
Includes bibliographical references and index.
lje 28/09/2018
Loans
Keywords: Economic history; Economic policy; Africa, Sub-Saharan.